2018
DOI: 10.1111/jcmm.13970
|View full text |Cite
|
Sign up to set email alerts
|

The contrary functions of lncRNA HOTAIR/miR‐17‐5p/PTEN axis and Shenqifuzheng injection on chemosensitivity of gastric cancer cells

Abstract: This study was implemented to figure out whether lncRNA HOTAIR/miR‐17‐5p/PTEN axis played a role that was opposite to Shenqifuzheng (SQFZ) injection in regulating the chemosensitivity of gastric cancer cells. The gastric cancer tissues were gathered and four gastric cancer cell lines were prepared, including BGC‐823, MGC‐803, SGC‐7901, and MKN28. Moreover, cisplatin, adriamycin, mitomycin, and 5‐fluoroura were managed as the chemo‐therapeutics, and SQFZ was prepared as a Chinese medicine. Striking distinctions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…HCP5 interacted with miR-3619-5p to regulate stemness and chemo-resistance in GC Next, regulatory mechanism of HCP5 in GC was explored. As widely reported, lncRNAs can function as miRNA sponge to regulate chemo-resistance in cancer cells 36,37 . Therefore, we searched for the target miRNAs for HCP5.…”
Section: Msc-induced Lncrna Hcp5 Facilitated Stemness and Chemo-resismentioning
confidence: 90%
See 2 more Smart Citations
“…HCP5 interacted with miR-3619-5p to regulate stemness and chemo-resistance in GC Next, regulatory mechanism of HCP5 in GC was explored. As widely reported, lncRNAs can function as miRNA sponge to regulate chemo-resistance in cancer cells 36,37 . Therefore, we searched for the target miRNAs for HCP5.…”
Section: Msc-induced Lncrna Hcp5 Facilitated Stemness and Chemo-resismentioning
confidence: 90%
“…LncRNAs are demonstrated to pose significant effects on the cancer-related metabolism, such as lipid metabolism and glycolysis, in a variety of cancer types 39,40 . Also, accumulating studies have attributed the development of chemo-resistance to aberrant expression of certain lncRNAs 37,38 . These discoveries suggested that MSCs might regulate chemoresistance in GC through altering expressions of lncRNAs, specifically the lncRNAs related to metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several microRNAs associated with chemoresistance are also involved in invasion and migration; thus, they are also important for metastasis [83,100,101,105,106,[109][110][111][112][113]120]. Some of microRNAs were involved in both metastasis and chemoresistance, as shown in Figure 2.…”
Section: Micrornas Associated With the Development Of Gc Chemoresistamentioning
confidence: 98%
“…By inhibiting PTEN, these microRNAs activate the PI3K/AKT/mTOR pathway and suppress apoptosis. A decrease in the expression of miR-17-5p and miR-147 inhibited proliferation, induced apoptosis, and increased the sensitivity of GC cells to chemotherapy [99,100]. A decrease in miR-193-3p expression inhibited proliferation and migration, and also increased the sensitivity of GC cells to 5-Fluorouracil (5-FU) in vitro and tumor growth in vivo [101].…”
Section: Micrornas Associated With the Development Of Gc Chemoresistamentioning
confidence: 99%